(3TQM efXheI GHf GdTMfIs - : (3eMH GdOjf eMeO Hf CHj HcQ GdYdhGfj GdMfajs ((3eMeO Hf CHj HcQ Hf OGhO GdYdhGfj, GdMehj, GdOeTbj, GdMfaj (B((3eMH GdOjf, CHh GdaVd(B) (3, J (B1016 (3g`s)
(3ChdgG (B:s
(3hHYO ajbhd abjQ Yah QHg bO GWdYfi HYV GdGUMGH Ydi gPg GdCQLhRI GdOQI GdhLjRI , hSCdfi Cf CTQMgG s
(3BNQgG (B:s
(3hSQTe ai GdfaS hCMSf GdGfJgGA s
(3aQZ ef JCdjag Sfg (B969 (3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B51 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B294s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B581s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3HdGZI (B236) s
Keywords: (3GdHdGZIs